Incorporation of cadmium sulfide quantum dots in photoactive layer of quaternary organic solar cell - Issa, Nour Attallah; Tan, Sin Tee; Chia, Chin Hua; Lau, Kam Sheng; Hj Jumali, Mohammad Hafizuddin; Chong, Kok-Keong; Yap, Chi Chin (Elsevier B.V., 2025)
Carbon quantum dots (CQDs) and cadmium sulfide (CdS) QDs have previously been used to enhance the photovoltaic performance of ternary organic solar cells (OSCs). Different from the previous reports, both CQDs and CdS QDs synthesized via the wet chemical route were incorporated into the photoactive layers of poly(3-hexylthiophene) (P3HT):(6,6)-phenyl-C61-butyric acid methyl ester (PC61BM) to construct quaternary OSCs in this work. The effects of incorporating both CQDs and CdS QDs in photoactive layers on the photovoltaic performance of OSCs were investigated in detail. The structure of the OSCs was fluorine tin oxide (FTO)/ZnO/photoactive layer/Ag. The ZnO electron transport layer in nanorod arrays form was prepared using hydrothermal method, whereas the photoactive layer was deposited using spin coating technique. The OSCs with CdS QDs demonstrated a power conversion efficiency (PCE) of 2.87 %, an increment of 12 % in comparison to that without CdS QDs. The introduction of CdS QDs not only improves light absorption but also increases the exciton dissociation and electron transport.